Bridging the gap between regenerative agriculture and the biological mechanisms controlling soil organic matter dynamics - Prairie, Aaron, author; Cotrufo, M. Francesca, advisor; Fonte, Steven, committee member; Rosenzweig, Steven, committee member; Hall, Edward, committee member (Colorado State University. Libraries, 2024)
This dissertation investigates the complex impacts of regenerative agriculture on soil organic matter (SOM) dynamics and soil fauna biodiversity, addressing a broad range of objectives from uncovering global patterns and policy needs to mechanistic understanding. Through global meta-analyses, policy evaluations, field studies, and mechanistic experiments, this research provides a comprehensive understanding of how regenerative practices influence soil health, carbon sequestration, and biodiversity. Chapter 2 aimed to understand global patterns through a meta-analysis quantifying the effects no-till (NT) and cropping system intensification significantly increase SOM, via impacts on both particulate organic matter (POM) and mineral-associated organic matter (MAOM). The analysis reveals that NT and cropping intensification synergize with integrated crop-livestock (ICL) systems to greatly enhance soil organic carbon (SOC) stocks, highlighting the potential of regenerative practices to mitigate climate change and promote soil health. Chapter 3 sought to evaluate the impacts of diversified agricultural systems on SOC, soil health, and yield across the United States. The findings indicate that diversified systems consistently show higher levels of SOC, improved soil health, and improved agronomic outcomes. The policy recommendations include increasing funding for soil health practices, supporting longer participation of producers in conservation programs, and tailoring these programs regionally to maximize their effectiveness. Chapter 4 focused on field-level impacts by examining the effects of varying degrees of regenerative practice adoption on SOM dynamics and soil fauna biodiversity in 22 farms within the Cheney Watershed, of central Kansas. By developing a Regenerative Farming Index (RFI), the study clearly links regenerative practices to increased carbon and nitrogen stocks in both POM and MAOM, and indicates a positive correlation between regenerative practices and soil biodiversity. Path analysis suggests that soil fauna indirectly influence SOM through their role in enhancing regenerative practices. Chapter 5 aimed to provide a mechanistic understanding of SOM dynamics by exploring the interactions between predatory mites and bacterivorous nematodes. The study highlights how these interactions shape microbial necromass accrual and MAOM formation. The findings underscore the importance of considering the entire soil food web in ecological studies to fully understand SOM formation and stabilization mechanisms. Overall, this dissertation advances the understanding of SOC dynamics under regenerative agriculture, providing valuable insights for sustainable soil management and climate change mitigation. By integrating global and local scales, it offers a holistic view of how regenerative practices can restore soil health and contribute to more resilient and productive agricultural systems.
Keywords: food web; soil fauna; soil organic matter; regenerative agriculture; agroecosystem; soil health